An Innovative Method for Large‐Scale Synthesis of Hexagonal Boron Nitride Nanosheets by Liquid Phase Exfoliation. Issue 40 (27th October 2020) - Mittal, Neha; Kedawat, Garima; Kanika,; Gupta, Sarika; Kumar Gupta, Bipin
Abstract: Hexagonal boron nitride nanosheets (h‐BNNSs), the geometry similar to that of two‐dimensional (2D) graphene has engrossed substantial attention due to its promising superior thermal, electrical, and dielectric properties for both fundamental studies as well as potential applications. Due to the strong covalent bond interactions in bulk hexagonal boron nitride (h‐BN), the high yield synthesis of large‐size h‐BNNSs is still a challenging task. In this report, a facile and innovative mixed solvent was carried out in the liquid phase exfoliation method via ultra‐sonication to obtain h‐BNNSs in large quality. The mixed solventconsisting of a mixture of Isopropyl alcohol (IPA) and De‐ionized (DI) water (in 3 : 7 ratio) is used for the highly efficient and cost‐effective synthesis of h‐BNNSs. In an optimized condition, the production yield of h‐BNNSs is approximately 90 % with a concentration of 0.6mg/mL. Here, the Lewis acid‐base interaction mechanism is responsible for the exfoliation of h‐BN due to the electron deficient boron atoms. The exfoliated ultra‐thin h‐BNNSs show better results, which is confirmed by Raman spectroscopy. Hence, our study provides a simple, large scale and economical exfoliation approach for the preparation of h‐BNNSs in next generation potential applications. Abstract : A facile, scalable and economical liquid phase exfoliation of bulk h‐BN powder has been demonstrated through ultra‐sonication method. The resulted h‐BNNSs are homogeneously dispersed in the IPA: DI solution without getting agglomerated. The SEM and TEM results confirmed the exfoliation of h‐BN nanosheets. Thus, this innovative method shows an inexpensive approach to produce large scale synthesis of high quality h‐BNNSs.